2007
DOI: 10.3168/jds.s0022-0302(07)71602-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Milk Flow Traits in Dairy Cows: Results of a Field Study

Abstract: The study of milk flow curves provides useful information for enhancing milking efficiency and protecting udder health by adapting milking machine and milking procedures to the physiological requirements of the cow. The aim of this experiment was to investigate, using field data, the relationships among traits of the milk flow curves, their sources of variation, and milking performances in terms of milk production, machine-on time, and udder health. A total of 2,486 milk flow curves of the whole udder were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
96
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 23 publications
(57 reference statements)
43
96
5
1
Order By: Relevance
“…of both systems were used according to the indication of the manufacturers and were not changed during the trial period. Sandrucci et al (2007) ascertained a HMF of 3.8±1.2 kg/min which was in agreement with the findings of the present study. Higher values of HMF with 4.49 kg/min and DMG with 2.84 kg/min, in comparison with our study, were found by Strapák et al (2009) at nearly the same level of MGG (15.63 kg).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…of both systems were used according to the indication of the manufacturers and were not changed during the trial period. Sandrucci et al (2007) ascertained a HMF of 3.8±1.2 kg/min which was in agreement with the findings of the present study. Higher values of HMF with 4.49 kg/min and DMG with 2.84 kg/min, in comparison with our study, were found by Strapák et al (2009) at nearly the same level of MGG (15.63 kg).…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that the milk letdown started earlier at the trial group milked quarter-individually. Sandrucci et al (2007) described a short tAN (0.89±0.47 min) that showed a wide variability similar to the present results for cows milked conventionally. Pre-stimulation positively influences the parameters of milk flow and therefore the efficiency of milk removal (Tančin et al 2007a).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, pre-milking preparation is essential to obtain a continuous and rapid milk removal of cisternal and alveolar milk and to avoid prolongation of milking time with consequent risk for udder health (Sandrucci et al, 2007) and teat-end callosity development (Neijenhuis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%